Evaluation of OPTIMISE (Online Programme to Tackle Individual's Meat Intake Through Self-regulation): Cohort Study - Cristina Stewart; Carmen Piernas; Kerstin Frie; Brian Cook; Susan A Jebb (JMIR Publications, 2022)
BackgroundThere is an urgent need to reduce society's meat consumption to help mitigate climate change and reduce noncommunicable diseases. ObjectiveThis study aimed to investigate changes in meat intake after participation in an online, multicomponent, self-regulation intervention. MethodsWe conducted a pre-post observational study among adult meat eaters in the United Kingdom who signed up to a website offering support based on self-regulation theory to reduce meat consumption. The program lasted 9 weeks (including a 1-week baseline phase, a 4-week active intervention phase, and a 4-week maintenance phase), comprising self-monitoring, goal setting, action planning, and health and environmental feedback. Meat intake was estimated during weeks 1, 5, and 9 using a 7-day meat frequency questionnaire. We analyzed the change in mean daily meat intake from baseline to week 5 and week 9 among those reporting data using a hierarchical linear mixed model. We assessed changes in attitudes toward meat consumption by questionnaire and considered the acceptability and feasibility of the intervention. ResultsThe baseline cohort consisted of 289 participants, of whom 77 were analyzed at week 5 (26.6% of the baseline sample) and 55 at week 9 (71.4% of the week 5 sample). We observed large reductions in meat intake at 5 and 9 weeks: -57 (95% CI -70 to -43) g/day (P<.001) and -49 (95% CI -64 to -34) g/day (P<.001), respectively. Participants' meat-free self-efficacy increased, meat-eating identities moved toward reduced-meat and non-meat-eating identities, and perceptions of meat consumption as the social norm reduced. Participants who completed the study reported high engagement and satisfaction with the intervention. ConclusionsAmong people motivated to engage, this online self-regulation program may lead to large reductions in meat intake for more than 2 months, with promising signs of a change in meat-eating identity toward more plant-based diets. This digital behavior change intervention could be offered to complement population-level interventions to support reduction of meat consumption.